2012
DOI: 10.2310/8000.2012.110554
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of advance directives among elderly patients attending an urban Canadian emergency department

Abstract: Introduction: To date, there has been minimal research on advance directives (ADs) among elderly patients in Canadian emergency departments (EDs). The purpose of this study was to determine the prevalence of ADs among elderly patients visiting an urban ED. We also explored whether there were factors associated with the existence of an AD and possible barriers to having one. Methods: This prospective study ran between October and December 2008. Individuals over the age of 70 who presented to the ED between 7 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In Australia in 2004, the prevalence of ADs in the general ED population was even lower (7.9%) than in our study [15]. In 2012, Gill et al published similar rates of ADs (19.3%) in the elderly urban Canadian ED population [16]. Further information on ADs in the ED was published in 2012 and focused only on senior or palliative care ED patients [17,18].…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…In Australia in 2004, the prevalence of ADs in the general ED population was even lower (7.9%) than in our study [15]. In 2012, Gill et al published similar rates of ADs (19.3%) in the elderly urban Canadian ED population [16]. Further information on ADs in the ED was published in 2012 and focused only on senior or palliative care ED patients [17,18].…”
Section: Discussionmentioning
confidence: 43%
“…The questionnaire was based on a previously developed and validated questionnaire and translated from English into German by a qualified translator [16]. The questionnaire contained demographic parameters that were personrelated such as age, gender, nationality, family status, level of education and living situation (appendix 1).…”
Section: Survey Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has examined availability of ACP documents during emergency care based on patient report. [7][8][9] The only study of ACP documentation availability within the electronic health record (EHR) for emergency department (ED) patients assessed availability during hospitalization, after admission orders had been placed. 10 The purpose of this study was to characterize and compare patient-reported completion of ACP preferences and real-time availability of ACP documentation in the EHR among older adults receiving care in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…1 We surveyed adult emergency department patients and found very similar results to those of Gill and colleagues published in this journal. 2 Twenty-four percent of patients in our study had completed an AD compared to 19.3% in their study. We also found that a very small percentage of patients brought their AD with them to the emergency department (5% in our study compared to 5.6%) and that more patients completed their ADs with the help of lawyers (55% in our study compared to 61.5%) rather than family physicians (5% in our study compared to 19.2%).…”
mentioning
confidence: 54%